Women's Struggle To Get The Equal Position With Men In Saudi Arabia By Carmen Bin Ladin In Inside The Kingdom Novel (2004): A Feminist Approach - Sulistyowati, Novita Agus; , Drs.Abdilah. Nugroho, M. Hum; , Drs. Sigit Haryanto M. Hum (2013)
The research is proposed to analyze the struggle for women's struggle to get the equal position with men in Saudi Arabia by Carmen Bin Ladin in Inside the Kingdom (2004) by a Feminist Approach. The research sets two objectives: the first is to analyze the novel in term of structural elements, and the second is to analyze the novel based on the Feminist Analysis. This study is a qualitative study using the novel of Inside the Kingdom as the object analysis of the study. There are two kinds of data sources: primary and secondary. The primary data source is the text of the novel Inside the Kingdom and the secondary data sources are some books and articles related to the subject. The method of collecting data in the research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study is as follows: first, structural analysis: Inside the Kingdom is a novel by Carmen which is written based on real event in live. Iniside the Kingdom novel by Carmen translated by Yusdi. M and published in 2006. The theme of this novel is "Freedom is woman's right to get the same position as men". Secondly, an individual psychological analysis: in this novel, Carmen wants to say that women need to struggle to get equal position with men and to get the freedom. Carmen wants to illustrate how women are subordinate in patriarchal society their life and that women's independence is not given but must be struggled for. Carmen wants to assert that in order to get their independence, women should rebel against patriarchal society in the issue of women's position, role, right, and participation.